Evidence of early systemic activation and transendothelial migration of neutrophils in neonates with severe respiratory distress syndrome - Sarafidis, Kosmas; Drossou-Agakidou, Vasiliki; Kanakoudi-Tsakalidou, Florence; Taparkou, Anna; Tsakalidis, Christos; Tsandali, Chaido; Kremenopoulos, Georgios (Pediatric pulmonology, 2001)
Several observations imply that the early inflammatory response involving activated neutrophils, tissue macrophages, and cytokines plays an important role in the pathogenesis of neonatal respiratory distress syndrome (RDS) and progression to bronchopulmonary dysplasia (BPD). The aim of this study was to test the hypothesis that changes in circulating neutrophil number and function and plasma levels of cytokines, consistent with neutrophil activation and migration to the tissues, occur during the early stages of neonatal RDS. For this purpose we measured peripheral blood levels of certain immunological parameters that promote neutrophil activation and transendothelial migration. Twenty preterm neonates with severe RDS and 20 healthy infants matched for gestational age were the subjects. The absolute neutrophil count (ANC), and plasma levels of interleukin‐6 (IL‐6), granulocyte colony‐stimulating factor (G‐CSF), and sL‐selectin using an enzyme‐linked immunosorbent assay (ELISA), neutrophil CD11b expression, and respiratory burst activity (RBA) using flow cytometry, were measured within 24 h after birth. The two groups were comparable regarding perinatal characteristics. None of the neonates studied had any clinical or laboratory evidence of infection by the time of blood sampling. The immunological investigation showed that the RDS neonates had significantly lower ANC (P = 0.032), higher expression of the CD11b on neutrophils (P = 0.0065), and higher G‐CSF and IL‐6 plasma levels (P = 0.0047 and P < 0.0001, respectively) in comparison to healthy preterm neonates. The neutrophil RBA and plasma sL‐selectin levels did not differ significantly between the two groups. We conclude that in neonates with severe RDS, there is evidence of a systemic neutrophil activation early in the course of the disease, supporting the view of a contributing role of activated neutrophils in the pathogenesis of RDS. Pediatr Pulmonol. 2001; 31:214–219. © 2001 Wiley‐Liss, Inc.